Vie et critique - Katia Genel (Recherches Germaniques)
The ‘Critical Theory’ of the Frankfurt School establishes a close link between life and criticism. The Frankfurt tradition describes the way in which the dysfunction of the social whole affects individuals, in terms of disease or pathology: it studies the conditions that make people sick and diagnoses social pathologies. This emphasis on life, disease, and pathology invites a comparison between the Frankfurt School and the thought of Georges Canguilhem. Such a comparison reveals points of convergence, in particular a methodological negativism that opens a critical point of view by focusing on the negative. In addition to highlighting elements of convergence, it also reveals important differences between the generations of the Frankfurt School with respect to the status accorded to disease and the conception of social criticism more generally.